Responses of avocado (Persea americana) to various doses of compost fertilizer and watering interval - Kansih Sri Hartini; Afifuddin Dalimunthe; Vinny Alvionita Br Tarigan; Aqilah Insani (Global Forest Journal, 2024)
Avocado is a multifunctional plant that can be utilized in all parts. The growth of avocado and its yield can be achieved by fulfilling requirements for the growth and maintenance of the plant well. Planting on dry land requires the addition of organic fertilizer and optimal water requirements to increase organic matter content and plant fertility. This research aims to obtain the optimal dosage of compost and watering intervals for the growth of avocado (Persea americana). The research was carried out in the Greenhouse Faculty of Agriculture, Universitas Sumatera Utara. This research used a factorial completely randomized design (F-CRD) with the addition of compost fertilizer doses (K0:0 kg, K1:0.5kg. K2: 1 kg. K3: 1.5 kg and K4: 2 kg) and watering intervals (A1: once a day. A2: once every three days. A3: once every five days and A4: once every seven days) with parameters of observation of height, diameter, top fresh weight, root fresh weight, top dry weight and root dry weight. The results showed that the interaction of compost and watering intervals significantly affected the height and diameter increase, root fresh weight, and root dry weight of avocado plants. The interaction of giving 1.5 kg of compost and watering intervals every day had the best effect on the growth and quality of avocado seedlings